THE INFLUENCE OF POLITICS IN ARMED CONFLICT IN AFRICA: CASE STUDY OF SOUTH SUDAN - Dr. Alier,; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The purpose of this study was to investigate the influence of politics in armed conflict in Africa Sudan. The study identified the possible ways though which politics could facilitate the public awareness about armed conflict in south Sudan.The research design adapted in this study was survey in which the researcher went to the field to collect data directly, sample size in this study was 50 response duty  there the researcher employed simple random sampling technique to select 100 respond duty from target population.Questionnaires and interview were used to collect data. Data analysis was presented in table with emphasis to frequencies and percentage, The finding, indicated that 58% and 29% of the respondents were agree and strongly agree respectively that influence is the power to have an important effect on someone of something.The results shows that 60% of the respondents have strongly agree and 30% of the respondents have agreed that politics is the set of activities that are associated with the governance of a country, state or area. 10% of the respondents have strongly agree. The results indicated that 58% and 10 of the respondents have strongly agree and agreed with statement that conflict is the consequence of a clash of interests between two parties, groups, or countries due to chasing contrasting or incompatible goal. The results indicated that 50% and 30% of the respondents have strongly agree and agreed with statement that armed is person that strengthens, protects, or increases efficiency the armed himself against the cold. The results indicated that majority of 28% of the respondents have strongly agree that armed usually occurs primarily as a result of a clash of interests in the relationship between parties groups and states furthermore, 20 others agreed with the statement. 32% were not sure with the above mentioned statement. The finding, 73% and 13.3% were strongly agree and agree accordingly with statement that on 24 June 2008, the south Sudan Air force was formally created by the southern Sudan legislative assembly.. Failure to address any conflict in a manner perceived as respecting citizens’ rights will lead to more conflicts. Violence begets violence. State intimidation and human rights abuse are a trigger of violence. Political effectiveness which measures government stability, was significant in reducing the number of political conflicts. This means that any regime has leadership turnover as leaders who overstay are likely to encourage citizens to force them out of office or the military to engage in a coup.